A comparison between cutting torque and resonance frequency in the assessment of primary stability and final torque capacity of standard and TiUnite single-tooth implants under immediate loading - Da Cunha, Hiron Andreaza; Francischone, Carlos Eduardo; Nary Filho, Hugo; Gomes De Oliveira, Rubelisa Cândido (My University, 2004)
Purpose: In this study, standard Brånemark System implants and Brånemark TiUnite implants were evaluated regarding primary stability and placement torque. The correlation between placement torque and primary stability as well as the influence of implant design on placement torque and primary stability were examined. Materials and Methods: Twelve patients who presented bilateral loss of either maxillary lateral incisors or premolars were treated with 24 immediately loaded dental implants. Each patient received 1 standard 3.75 x 13-mm Brånemark System implant and one 3.75 x 13-mm TiUnite Mk III implant. One at a time, each implant was connected by a transducer to an Osstell machine that automatically translated a resonance frequency value for the implant into an implant stability quotient value. Osseocare equipment was used to measure the placement torque for both types of implants. Results: Statistical analysis showed higher mean values for standard implants in relation to placement torque and resonance frequency values. Discussion: There was no overall correlation between placement torque and resonance frequency values; this finding supported previous studies. Conclusion: Stability was shown to be higher for the standard implants. Mean values of torque resistance were higher for the standard implants than for the TiUnite implants. Implant design appeared to influence primary stability and placement torque.
Keywords: Dental implants; Immediate loading; Placement torque; Resonance frequency